2020
DOI: 10.1021/acs.cgd.0c00689
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Aminopyridines: Synthesis, Structure, and Rare Liquid–Liquid Cocrystal Formation Driven by Unusually Short N–H···F–C Hydrogen Bonding

Abstract: The role of hydrogen bonding in the crystal packing of a series of 4-aminoperfluoropyridines was studied using single-crystal X-ray crystallography. The aminoperfluoropyridines were synthesized using only excess amine to serve as both nucleophile and base. Instead of addition to the perfluoropyridine ring, a strong N–H···F–C hydrogen bond led to cocrystal formation of perfluoropyridine with sterically hindered amines dicyclohexylamine as well as 2-methylpiperdine. This formation is, to our knowledge, the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Further interest lies in the fact that both of the pure components are liquids at room temperature. This 'liquid-liquid co-crystallization' has been observed previously, but to my knowledge, it does not abound (Peloquin et al, 2020).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Further interest lies in the fact that both of the pure components are liquids at room temperature. This 'liquid-liquid co-crystallization' has been observed previously, but to my knowledge, it does not abound (Peloquin et al, 2020).…”
supporting
confidence: 59%
“…When this odd couple of two quite different molecules do form the solid, though, they apparently do so readily, yielding centimetres-long rod-shaped crystals.Further interest lies in the fact that both of the pure components are liquids at room temperature. This 'liquid-liquid co-crystallization' has been observed previously, but to my knowledge, it does not abound (Peloquin et al, 2020).I might refer to the new solid as a co-crystal to reflect the observation that H 2 O is a full structural partner and is not merely present as a dispensable solvate. However, that would risk venturing into the definition of a co-crystal, a complex subject that has been treated more fully by others (Bond, 2007;Parkin et al, 2008;Aitipamula et al, 2012).Beyond the existence of the channel lined by water is the suggestive fact that there is disorder among the sites of the water hydrogen atoms.…”
mentioning
confidence: 53%
“…Perfluoropyridine (C 5 NF 5 ; PFPy) is an ideal candidate to use in the preparation of complex fluorinated compounds and materials as PFPy is reactive towards nucleophilic addition (Sandford, 2012). Furthermore, our group and others have demonstrated that this addition can be regio-selectively controlled, with stoichiometric addition to the 4-(para-) position being exclusive with a broad range of nucleophiles (Brittain & Cobb, 2019;Peloquin et al, 2020;Seyb & Kerres, 2013). Sequential addition can also be accomplished at the 3,5-(meta-) positions (Corley et al, 2019;Houck et al, 2021).…”
Section: Chemical Contextmentioning
confidence: 91%
“…2-[(Perfluoropyridin-4-yl)amino]ethan-1-ol was synthesized using a known method and used without further purification (Peloquin, et al, 2020). Methacryloyl chloride was purchased from Sigma and distilled under reduced pressure prior to use.…”
Section: Synthesis and Crystallizationmentioning
confidence: 99%